Detection of anti-isoniazid and anti-cytochrome P450 antibodies in patients with isoniazid-induced liver failure - Imir G. Metushi; Corron Sanders; William M. Lee; Anne M. Larson; Iris Liou; Timothy J. Davern; Oren K. Fix; Michael L. Schilsky; Timothy M. McCashland; J. Eileen Hay; Natalie Murray; A. Obaid S. Shaikh; et al. (2013)
Isoniazid (INH)-induced hepatotoxicity remains one of the most common causes of drug-induced idiosyncratic liver injury and liver failure. This form of liver injury is not believed to be immune-mediated because it is not usually associated with fever or rash, does not recur more rapidly on rechallenge, and previous studies have failed to identify anti-INH antibodies (Abs). In this study, we found Abs present in sera of 15 of 19 cases of INH-induced liver failure. Anti-INH Abs were present in 8 sera; 11 had anti–cytochrome P450 (CYP)2E1 Abs, 14 had Abs against CYP2E1 modified by INH, 14 had anti-CYP3A4 antibodies, and 10 had anti-CYP2C9 Abs. INH was found to form covalent adducts with CYP2E1, CYP3A4, and CYP2C9. None of these Abs were detected in sera from INH-treated controls without significant liver injury. The presence of a range of antidrug and autoAbs has been observed in other drug-induced liver injury that is presumed to be immune mediated. Conclusion: These data provide strong evidence that INH induces an immune response that causes INH-induced liver injury. (Hepatology 2014;59:1084–1093)